2002
DOI: 10.1111/j.1530-0277.2002.tb02611.x
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Alcohol Response Differs in Heavy Versus Light Drinkers

Abstract: Background: Most studies of risk factors for alcohol-related problems have focused on biological family history as a primary risk factor. However, other factors, such as early-age heavy drinking, are also risk factors for sustained or progressive heavy consumption. Little is currently known about the mechanisms underlying binge or heavy drinking.Methods: This study examined the acute subjective and objective effects of ethanol in heavy drinkers versus light drinkers. Thirty-four subjects participated in this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
90
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(100 citation statements)
references
References 61 publications
8
90
1
1
Order By: Relevance
“…Thus, heightened sensitivity to the acute stimulant effects of methamphetamine appears to confer protection against high levels of methamphetamine, cocaine and ethanol self-administration. This result is opposite to that predicted from the human literature on alcohol that has suggested that greater sensitivity to the behavioral stimulant effects of alcohol is associated with a positive family history of alcoholism (Newlin and Thomson, 1999) and with heightened levels of alcohol consumption (Holdstock et al, 2000;King et al, 2002). However, it is possible that with methamphetamine, there is a biphasic relationship such that modest levels of stimulation are pleasant and extreme levels aversive.…”
Section: Selected Linescontrasting
confidence: 64%
See 1 more Smart Citation
“…Thus, heightened sensitivity to the acute stimulant effects of methamphetamine appears to confer protection against high levels of methamphetamine, cocaine and ethanol self-administration. This result is opposite to that predicted from the human literature on alcohol that has suggested that greater sensitivity to the behavioral stimulant effects of alcohol is associated with a positive family history of alcoholism (Newlin and Thomson, 1999) and with heightened levels of alcohol consumption (Holdstock et al, 2000;King et al, 2002). However, it is possible that with methamphetamine, there is a biphasic relationship such that modest levels of stimulation are pleasant and extreme levels aversive.…”
Section: Selected Linescontrasting
confidence: 64%
“…The focus on acute stimulant effects may be better supported by the idea that initial drug sensitivity influences continued drug use and thus, susceptibility to the development of drug abuse and addiction. This relationship has been strongly supported for alcohol (Heath et al, 2001;Holdstock et al, 2000;Newlin and Thomson, 1999;Poikolainen, 2000;Schuckit and Smith 2000;King et al, 2002), and there are some intriguing results for psychostimulants as well. For example, the initial stimulant response to amphetamine predicted the likelihood of further drug use (de Wit et al, 1986;Gabbay, 2003), and for cocaine, there was a significant positive relationship between subjects' ratings of positive cocaine effects, including euphoria, and lifetime cocaine use (Davidson et al, 1993).…”
Section: Acute Locomotor Stimulationmentioning
confidence: 84%
“…Individuals at-risk for AUDs typically report diminished subjective experiences or 'low-level responses' (LLRs) to alcohol administration (Trim et al, 2009;Schuckit and Smith, 2011) although this has not been found across all studies (eg, King et al, 2002). LLRs at ages 19 and 20 predict AUDs at 10-and 8-year follow-up, respectively (Volavka et al, 1996;Schuckit and Smith, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The 'differentiator' model proposes that individuals at-risk for AUDs experience enhanced stimulant effects during the ascending limb of the blood alcohol curve and diminished sedative effects during the descending limb (reviewed in Ray et al, 2010;Newlin and Thompson, 1990;Newlin and Renton, 2010). Although there remains some uncertainty about which precise dimension of individuals' subjective reactions to alcohol is most predictive of subsequent AUDs (King et al, 2002(King et al, , 2011, there is consensus that some aspect of individual subjective response mediates the risk forFand development ofFAUDs, making such response profiles potentially interesting endophenotypes (Morean and Corbin, 2010;Ray et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…To date, no research appears to have examined such potential priming effects of AMPH in this population. In healthy volunteers, alcohol itself can induce both stimulant and sedative effects (Boerngen-Lacerda and Souza-Formigoni, 2000;King et al, 2002;Martin et al, 1993;Schechter and Lovano, 1982). Correlational evidence also indicates some correspondence in the subjective effects of alcohol and AMPH in healthy volunteers (Holdstock and de Wit, 2001).…”
Section: Introductionmentioning
confidence: 99%